Aplicativo web de gestión de historias clínicas electrónicas para los usuarios de la Clínica Especializada Emanuel, San Juan Bautista 2021 - Bartens Lopez, Jorge Augusto (2022)
The development of information and communication technologies has shaped the different ways of working for different companies. The Emanuel Specialized Clinic, with the aim of improving the services provided by users, implemented a web application for the management of electronic medical records in order to improve the service. In this context, the question was: How does the development and implementation of a web application for the management of electronic medical records improve the quality of the service in the Emanuel Specialized Clinic, San Juan Bautista 2021? To answer the question, the specific objectives were to evaluate, before and after implementation, and to compare these results. The study is quantitative, analytical, quasi-experimental, with a pre and post test to determine how the quality of service improves. The sample universe consisted of 18 users (08 doctors, 04 nurses, 03 technicians and 03 administrative staff); The survey was carried out considering the dimensions of satisfaction, time and efficiency. The SUS was used for satisfaction; for time, the categories fast (from 10 to less than 15 minutes), normal (from 15 to less than 25 minutes) and delay (from 25 to 35 minutes); and for efficiency the categories a lot of material and little or no material were used. The relevant results are that, with the use of the web application, satisfaction improves, time is reduced and little or no material is used in EHR management. For such statements, for satisfaction and efficiencies, the non-parametric Chi square statistic of homogeneity was applied; and for time the parametric statistics t - student. It was concluded that, with the development and implementation of a web application for the management of electronic medical records, the quality of service improves at the Emanuel Specialized Clinic, San Juan Bautista 2021.